Modelling of msmacomponents: Porous pavement with detention system underneath for low traffic roads - Mah, D.Y.S.; Boon, Yee Koh; Putuhena, F.J.; Nor Azalina, Rosli (JCECT, 2016)
This study has been made in order to pursue practices in Water Sensitive Urban Design (WSUD), where stormwater management becomes a mainstream in Malaysia. The main focus of this study is to develop a stormwater conveyance model incorporating porous pavement and on-site detention system at Heights Drive (Stutong), Kuching City, and to investigate its effectiveness. Conventional pavements are impervious and create contaminated runoff. In contrast, combination of porous pavement with storage as WSUD approach allows stormwater to percolate to an underlying detention system where stormwater is both infiltrated to underlying clay soil and discharged with a lower rate to drain beside the road. Nine roads with total surface area of 12,660 m2 are selected and a total of 6 scenarios are modelled and simulated using EPA’s SWMM 5.0. It is found that the peak discharge at outfall from the study area is decreased by 23%, in which 2% of the stormwater is infiltrated to the ground for groundwater recharge.